Tensile Properties of Hybrid Sugar Palm/Kenaf Fibre Reinforced Polypropylene Composites - Bachtiar, Dandi; Siregar, J. P.; Ahmad Shahrizan, Sulaiman; M. R. M., Rejab (Trans Tech Publications, Switzerland, 2014)
Study on hybridization of two types of natural fibres reinforced thermoplastic composites was an alternative option in research on natural composites. This paper presents the investigation on tensile properties of combining sugar palm and kenaf fibres reinforced polypropylene composites. The hybrid composites were prepared with different amounts of fibres (i.e. 10%, 20% and 30% by weight percent) while the ratios between sugar palm and kenaf fibre are 30:70, 50:50 and 70:30. The composites have been fabricated using melt mixer technique and followed by compression molding process. The specimens were cut according ASTM Standard D638 for conducting the tensile testing. The results shown that tensile strength of composites tend to decreased when the content of loading fibres increased. Among the composites with different ratios, the hybrid composites that contain more kenaf fibres exhibit the higher value in tensile strength than the composites that contain more sugar palm fibres.